L’ethos collectif des professeurs documentalistes sur Twitter : exploration de quelques pratiques - Florence Thiault (Itinéraires)
The article presents the findings of a study on the use of a digital social network Twitter in ethos of a specific professional community. This study is based on a corpus of profils from users belonging to the community of school librarian teachers. The digital social network Twitter has become a strategic tool for users, whose socialization and professional commitment. The semiotic model of digital identity is applied to identify the various digital ethos of these professionals.